Qadhâyâ al-Mar’ah fî al-Qur’ân ‘inda Bedîuzzamân Sa’îd al-Nûrsi fî Risaleî Nûr - Sujiat Zubaidi Shaleh; Ridani Faulika Permana (Universitas Darussalam Gontor, 2019)
This paper discusses about the problems of women in the Qur’an according to the perspective of Bediuzzaman Sa’id Nursi in his phenomenal book “Risale-i Nur”. Women in Islam have a respectable role and position. But as development of technology, the situation degenerated as the Jahiliyyah woman’s habits were cultivating. To examine the problems of women, especially in the Qur’an, the authors use thematic studies and descriptive analysis. So that it can be explained some of the problems of women discussed by Bediuzzaman Said Nursi; namely the nature of women, treatise on hijab, polygamy, inheritance rights and improvement of offspring. The nature of woman born of her love is a pioneer of compassion according to Nursi, especially from the sense of sacrifice for his children. Hijab according to Nursi is every woman’s needs based on her nature, because women according to their nature are not comfortable to show their aurat to the opposite sex who is not the mahram not as barrier but to avoid danger. Likewise Nursi looked at polygamy, he allowed with strict requirements because the purpose of marriage according to Nursi is to increase the number improve the heredity. finally it will maintain the type of human population. Based on the purpose of marriage which is not only to satisfy lust. This is the deifference between human and animals in general. So that inheritance rights can bring improvements and benefits. There is no inheritance except by marriage in accordance with the Shari’a. because the marriage string which is according to Nursi will lead to a positive tendency. As for the improvement of offspring who not only produce heredity. So it is meaningfull with help and support each other.